2019
DOI: 10.1002/dc.24175
|View full text |Cite
|
Sign up to set email alerts
|

The key radiologic and cytomorphologic features of oncocytic and oncocytoid lesions of the salivary gland

Abstract: Oncocytic and oncocytoid lesions represent a distinct subset of salivary gland lesions. True oncocytic lesions of the salivary gland are entirely composed of oncocytes. These are characterized by the presence of abundant eosinophilic granules due to the presence of abundant cytoplasmic mitochondria. Oncocytic lesions of the salivary gland include oncocytosis, oncocytoma, and oncocytic carcinoma. In addition to the true oncocytic lesion, there exists another group of salivary gland lesions, which demonstrate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 155 publications
(340 reference statements)
0
8
1
Order By: Relevance
“…On surgical follow‐up of oncocytic/oncocytoid SUMP, the most common benign neoplasm was Warthin tumor (22.8%), followed by oncocytoma (10.9%), and the most common malignant diagnosis was mucoepidermoid carcinoma (22.8%), followed by acinic cell carcinoma (14.9%). In typical cases, the FNA diagnosis of the previously mentioned tumors is usually straightforward 11,24‐27 . Occasional cases lacking classic cytomorphologic features, particularly those with superimposed reactive or metaplastic changes, would be placed in SUMP under this subcategory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On surgical follow‐up of oncocytic/oncocytoid SUMP, the most common benign neoplasm was Warthin tumor (22.8%), followed by oncocytoma (10.9%), and the most common malignant diagnosis was mucoepidermoid carcinoma (22.8%), followed by acinic cell carcinoma (14.9%). In typical cases, the FNA diagnosis of the previously mentioned tumors is usually straightforward 11,24‐27 . Occasional cases lacking classic cytomorphologic features, particularly those with superimposed reactive or metaplastic changes, would be placed in SUMP under this subcategory.…”
Section: Discussionmentioning
confidence: 99%
“…First, "clear cell" is generally used to describe the artifactual clearance of a cell's cytoplasm resulting from formalin fixation in histology and the corresponding cellular morphology in cytologic preparation is mostly oncocytoid cells with granular, foamy, or vacuolated cytoplasm, overlapping with the oncocytic/oncocytoid subcategory. 4,10,11 Second, no SUMP cases were classified as cellular neoplasm with clear cell features in the previous series. [4][5][6][7][8][9][10] In addition, we created a new "not otherwise specified (NOS)" subcategory to accommodate SUMP cases that are neither basaloid nor oncocytic/oncocytoid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degenerative oncocytes are common in the epithelial layer and spill into the fluid of the lumen. This condition commonly occurs in WT and indicates the apoptosis of oncocytes in the luminal fluid [7,11], and these degenerated oncocytes may resemble squamous cells [16]. The percentages of degenerated oncocytic cells were 65% and 66% in the studies of Flezar et al and Viguer et al [4,11].…”
Section: Discussionmentioning
confidence: 92%
“…Oncocytes are typical cell components of WT but excessive presence of oncocytic cells in the field may lead to a diagnostic mistake such as oncocytoma [15][16][17]. Werma et al reported that oncocytic epithelial cells are more often seen as papillary fragments, sheets, acini, and isolated appearances in cases of oncocytoma.…”
Section: Discussionmentioning
confidence: 99%